Emergency trauma care during the outbreak of corona virus disease 2019 (COVID-19) in China - Yang Li; Ling Zeng; Zhanfei Li; Qingxiang Mao; Ding Liu; Letian Zhang; Huayu Zhang; Yu Xie; Guo Liu; Xiaoqin Gan; Fan Yang; Siru Zhou; et al. (World Journal of Emergency Surgery, 2020)
Abstract Background A novel coronavirus pneumonia outbreak began in Wuhan, Hubei Province, in December 2019; the outbreak was caused by a novel coronavirus previously never observed in humans. China has imposed the strictest quarantine and closed management measures in history to control the spread of the disease. However, a high level of evidence to support the surgical management of potential trauma patients during the novel coronavirus outbreak is still lacking. To regulate the emergency treatment of trauma patients during the outbreak, we drafted this paper from a trauma surgeon perspective according to practical experience in Wuhan. Main body The article illustrates the general principles for the triage and evaluation of trauma patients during the outbreak of COVID-19, indications for emergency surgery, and infection prevention and control for medical personnel, providing a practical algorithm for trauma care providers during the outbreak period. Conclusions The measures of emergency trauma care that we have provided can protect the medical personnel involved in emergency care and ensure the timeliness of effective interventions during the outbreak of COVID-19.